Elmidae of Sarawak: the genus Potamophilus Germar, 1811, with a description of P. kelabitensis sp. nov. (Insecta: Coleoptera) - Kodada, Ján; Boukal, David S.; Vďačný, Peter; Goffová, Katarína; Ondrejková, Kamila (European Journal of Taxonomy, 2022)
Potamophilus kelabitensis sp. nov., a new riffle beetle (Coleoptera, Elmidae) discovered in the Kelabit Highlands (northern Sarawak) and Sapulut environment (southern Sabah), is described. Illustrations of the habitus and diagnostic characters of the new species are presented. Differences from the type species P. acuminatus (Fabricius, 1792) from the Palaearctic region, based on DNA barcodes and morphological characters, are discussed. Selected morphological characters of all known species of Potamophilus from Vietnam, Myanmar, and Papua New Guinea are also compared with the new species. The systematic position of the genus relative to other sympatric genera of the subfamilies Larainae LeConte, 1861 and selected Elminae Curtis, 1830 belonging to three tribes is discussed based on phylogenetic trees inferred from the mitochondrial COI and nuclear ArgK as well as 18S rRNA gene sequences.